(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
The deliberate inhalation of solvents among children and adolescents for “Kicks” is becoming more common in our country. The particular agent abused seems to be largely a function of availability. The typical inhalant abuser is a teenage male who is attracted to solvent because of their euphoric and hallucinogenic properties and the fact that they are cheap, legal and easily obtainable.1 It is generally regarded as a relatively harmless practice and consequently little attention had been paid to the isolation of the toxic agent from the variety of substance used.2 It is well recognized that solvent abuse results in sudden death due to plastic bag suffocation but one such case not associated to it but has resulted in death due to aspiration is being discussed